2021
DOI: 10.3390/ani11123459
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Acute Phase Reaction, Cortisol, and Haematological Parameters in Ewes in the Periparturient Period

Abstract: A well-functioning immune system is the basis for protection against infectious and metabolic diseases, and a smooth return to homeostasis. The periparturient period is considered critical because major changes in the endocrine, behavioural, digestive, and immune systems dysregulate immune function, leading to immunosuppression. With age, the immune system could become dysregulated. The purpose of the present investigation was to compare changes in plasma concentrations of acute phase proteins, cortisol, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…Основен приоритет е да се определят стандартните параметри за нестресирани животни, отглеждани във всяка отделна страна и/ или географска и климатична зона, чрез изграждане на референтна таблица с местни данни за хематологични параметри, които трябва да се актуализират периодично, за да се направи правилно сравнение (Ouanes et al, 2011, Bezerra et al, 2017, Greguła-Kania et al, 2021. От друга страна, изследването на литературни източници, свързани с влиянието на екстремни стойности на факторите на околната среда върху хематологичните и биохимичните показатели, може да предостави ценна информация за възможностите за адаптация на избраната порода (Rahman et al, 2018, Khalil et al, 2022.…”
Section: въведениеunclassified
“…Основен приоритет е да се определят стандартните параметри за нестресирани животни, отглеждани във всяка отделна страна и/ или географска и климатична зона, чрез изграждане на референтна таблица с местни данни за хематологични параметри, които трябва да се актуализират периодично, за да се направи правилно сравнение (Ouanes et al, 2011, Bezerra et al, 2017, Greguła-Kania et al, 2021. От друга страна, изследването на литературни източници, свързани с влиянието на екстремни стойности на факторите на околната среда върху хематологичните и биохимичните показатели, може да предостави ценна информация за възможностите за адаптация на избраната порода (Rahman et al, 2018, Khalil et al, 2022.…”
Section: въведениеunclassified
“…An interesting study of the differences in hematological and biochemical parameters in Pramenka sheep raised at different altitudes in Bosnia and Herzegovina was done by Hrković-Porobija et al (2019). They found that almost all of the biochemical parameters showed variations between the sampling areas that could be caused by the influence of different geographic areas and floristic composition, as well as the current health status of the examined individuals, but calculated correlative values showed significant differences for individual hematological and biochemical parameters in sheep for both investigated areas.…”
Section: Introductionmentioning
confidence: 99%
“…A crucial priority is to define the standard parameters for non-stressed animals reared in each individual country and/or geographic and climatic zone, by building a reference table with local data of hematological parameters, which should be updated periodically to make a proper comparison (Ouaneset al, 2011,Bezerra et al, 2017, Greguła-Kania et al, 2021. On the other hand, the study of literary sources related to the influence of extreme values of environmental factors on hematological and biochemical indicators can provide valuable information about the adaptation possibilities of selected breed (Rahman et al, 2018,Khalil et al, 2022.…”
Section: Introductionmentioning
confidence: 99%